An Inertial Proximal-Gradient Penalization Scheme for Constrained Convex Optimization Problems - Boţ, Radu Ioan; Csetnek, Ernö Robert; Nimana, Nimit (Vietnam journal of mathematics, 2018)
We propose a proximal-gradient algorithm with penalization terms and inertial and memory effects for minimizing the sum of a proper, convex, and lower semicontinuous and a convex differentiable function subject to the set of minimizers of another convex differentiable function. We show that, under suitable choices for the step sizes and the penalization parameters, the generated iterates weakly converge to an optimal solution of the addressed bilevel optimization problem, while the objective function values converge to its optimal objective value.